2011
DOI: 10.1007/s13312-012-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency as a risk factor for simple febrile seizures-A case control study

Abstract: Iron deficiency is a significant risk factor for simple febrile seizures in children of age group 6 months to 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 13 publications
4
14
1
Order By: Relevance
“…In present study mean Hb, MCV and MCH was 8.92g%, 67.03 fl, 30.66 pg respectively which was significantly low in cases and compared to control. Kumari PL et al 24 and Naveed-ur-Rehmann et al 25 had results similar to our study. (Table-3) In present study, there was variation of the iron level with FS and FI group.…”
Section: Results and Observationssupporting
confidence: 91%
“…In present study mean Hb, MCV and MCH was 8.92g%, 67.03 fl, 30.66 pg respectively which was significantly low in cases and compared to control. Kumari PL et al 24 and Naveed-ur-Rehmann et al 25 had results similar to our study. (Table-3) In present study, there was variation of the iron level with FS and FI group.…”
Section: Results and Observationssupporting
confidence: 91%
“…Many authors point out that iron deficiency anemia in children is an important risk factor of the febrile seizures. This risk is higher in children with SFS between the ages of 6 months and 3 years (Derakhshanfar, Abaskhanian, Alimohammadi, & ModanlooKordi, 2012; Fallah, Tirandazi, Akhavan Karbasi, & Golestan, 2013; Kumari, Nair, Nair, Kailas, & Geetha, 2012; ur Rehman & Billoo, 2005; Sadeghzadeh, Khoshnevis Asl, & Mahboubi, 2012; Sherjil, us Saeed, Shehzad, & Amjad, 2010). A Sherjil et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results have been repeated in other studies such as those carried out by Kumari et al . [12] Momen et al . [18] and Naveed al-Rahman and Billoo.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Studies conducted on the role of iron deficiency in febrile convulsion have yielded completely conflicting results. In some of these studies, iron deficiency has been identified as a risk factor,[71213] while in others it has been stated that iron deficiency increases the threshold of neuron excitation and thus can play a protective role against febrile convulsion. [1415] Given these contradictory results, we decided to study the relationship between iron deficiency anemia and febrile convulsion in children hospitalized in Amir Kabir Hospital of Arak City.…”
Section: Introductionmentioning
confidence: 99%